Penerapan Kebijakan Kurikulum Merdeka Untuk Belajar Di Sekolah - Nasution, Marwiyah; Lubis, Marito; Nurmala, Mona Septi; Gusmaneli (Jurnal Ilmu Manajemen dan Pendidikan | E-ISSN : 3062-7788, 2025)
This study aims to analyze the implementation of the Merdeka Curriculum policy in Senior High Schools (SMA), with a particular focus on its relevance to the educational transformation following the Covid-19 pandemic. The Merdeka Curriculum was introduced as a strategic response by the Indonesian government to address the significant learning loss experienced during the pandemic through flexible, differentiated, and student-centered learning approaches. This research employs a qualitative descriptive method, relying entirely on online observation, in-depth document analysis, and a review of digital educational resources. No direct field interviews were conducted; instead, data were obtained from scientific literature, official government publications, and online learning activities documented by various Senior High Schools in Indonesia. The findings indicate that the Merdeka Curriculum offers substantial opportunities for post-pandemic learning recovery, especially through strengthened project-based learning, diagnostic assessments, and adaptive instructional design that aligns with students’ needs. However, its implementation still faces several obstacles, including the widening digital literacy gap among teachers and students during the pandemic, inadequate technological infrastructure in remote areas, and limited teacher understanding of formative assessment and differentiated instruction. Despite these challenges, the Merdeka Curriculum has demonstrated positive impacts on students’ creativity, motivation, independence, and character development guided by the Profile of Pancasila Students. In conclusion, the implementation of the Merdeka Curriculum in the post-Covid-19 era represents an essential step in rebuilding Indonesia’s education system toward more flexible, humanistic, and relevant learning. Its success is largely determined by the readiness of human resources, the extent of government support, the enhancement of teachers’ digital competence, and collaborative efforts among schools, families, and communities in addressing the challenges of post-pandemic education.